Legal Protection for Victims of Motor Vehicle Purchase as A Result Of Act Criminal Theft - Achmad Surya (RESAM Jurnal Hukum, 2023)
In a transaction of buying and selling goods, people are sometimes and mostly interested in goods that are sold below market price. However, sometimes the desire to obtain a difference or profit, if not careful, can ensnare the buyer in criminal law matters, namely the act of cheating. The purpose of this research is to determine legal protection for victims of motor vehicle purchases resulting from criminal acts of theft by Bener Meriah District Police Investigators. This research is normative law with a case approach method and statutory regulations. The data source used is secondary data obtained from primary legal materials, secondary legal materials and tertiary legal materials. The data that has been collected is processed in the form of qualitative analysis. After the data is analyzed one by one, it is then arranged systematically so that it can answer the problems of this research. The research results explain. Legal protection for victims of purchasing motorized vehicles resulting from criminal acts of theft, currently cannot be fulfilled according to criminal law and witness and victim protection laws, victims can become suspects if the purchaser of the vehicle actually knew that the vehicle was obtained as a result of a crime or reasonably thought that The vehicle is the result of a crime, for which the buyer can be charged under Article 480 of the Criminal Code (KUHP).